2016
DOI: 10.1586/14760584.2016.1131127
|View full text |Cite
|
Sign up to set email alerts
|

Development of a schistosomiasis vaccine

Abstract: Summary Schistosomiasis is a neglected tropical disease (NTD) of public health importance. Despite decades of implementation of mass praziquantel therapy programs and other control measures, schistosomiasis has not been contained and continues to spread to new geographic areas. A schistosomiasis vaccine could play an important role as part of a multifaceted control approach. With regards to vaccine development, many biological bottlenecks still exist: the lack of reliable surrogates of protection in humans; im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
95
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 87 publications
0
95
0
3
Order By: Relevance
“…Over 240 million people are estimated to be currently infected worldwide with the majority being school aged children (Barry et al 2013; Molehin et al 2016). Experts in the field believe that the current estimate of the burden of schistosomiasis is most likely between 400 and 600 million (Hotez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 240 million people are estimated to be currently infected worldwide with the majority being school aged children (Barry et al 2013; Molehin et al 2016). Experts in the field believe that the current estimate of the burden of schistosomiasis is most likely between 400 and 600 million (Hotez et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sm-p80 is expressed in intra-mammalian stages of the parasite and has been localized to the parasite surface syncytium making it an attractive target of host immunity (Braschi and Wilson 2006; Kumagai et al 2005). With respect to the schistosomiasis vaccine development, Sm-p80 is now considered one of the leading candidates (Mo et al 2014; Molehin et al 2016). Several studies by our group have shown that Sm-p80 vaccine is highly efficacious against S. mansoni infections in mice and baboons (Ahmad et al 2009a; Ahmad et al 2009b; Ahmad et al 2009c; Karmakar et al 2014b; Le et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…humans, Figure 2), hence, even a partial reduction in worm burden against cercarial infections would be a significant advance. This is because a vaccine that reduces the number of parasites will ultimately reduce egg-induced pathology and transmission rates of the infection [10;21-27]. Over the last 20 years, several different groups of schistosome experts have made recommendations to this effect.…”
Section: Current Status Of Schistosomiasis Vaccinesmentioning
confidence: 99%
“…To date only three schistosome vaccine candidates are in Phase I to Phase III trials [10;27;36]. These include S. haematobium 28-kD glutathione S-transferase (rSh28GST), S. mansoni 14-kDa fatty acid-binding protein (Sm14) and S. mansoni tetraspanin, a 9-kDa surface antigen (Sm-TSP-2) [10;27;36].…”
Section: Current Status Of Schistosomiasis Vaccinesmentioning
confidence: 99%
“…Introduced in the early 1980s, praziquantel (PZQ) is the drug of choice to reduce morbidity and mortality due to schistosomiasis, but its large-scale use might be associated with the onset of resistance (3). Currently, no vaccine for schistosomiasis is commercially available, though a few candidates are in clinical trials (4). At present, the control of schistosomiasis is dependent on chemotherapy, but it is not ideal to have only one effective treatment.…”
mentioning
confidence: 99%